Bombay Samachar building - Ghosh, Ayan (2023)
Bombay Samachar was established in 1822, making it the oldest continuously published newspaper in India. The bilingual newspaper was published in Gujarati and English. It was founded by Fardunjee Marzban, the first Indian editor of a newspaper who also established the first vernacular printing press in India and the production of Gujarati type.